ROLE OF DEBRIEFING AS A LEARNING TOOL IN SIMULATION BASED LEARNING FOR STUDENTS OF PRECLINICAL YEARS AT THE END OF TWO CONSECUTIVE MODULES-INITIAL EXPERIENCE - Ali, Liaqat; Nisar, Sabina; Ghassan, Ayesha (Journal of Ayub Medical College Abbottabad, 2015)
Background: The topic of debriefing has been receiving some attention in the simulation literature. Because of the significance of debriefing on learning, evaluation of the de-briefer is done to ensure optimal performance. Structured debriefing as a learning tool was evaluated at the end of modular teaching of first year MBBS. This study is a descriptive cross sectional study to analyze the usefulness of debriefing as an instructional strategy during observed structured clinical examination conducted at the end of two consecutive modules of first year MBBS students. Methods: Performance of 150 students of first year MBBS was evaluated at the end of modules called Foundation module and skin and musculoskeletal module. Debriefing was structured and conducted after training of six staff members who conducted and supervised Objectively Structured Clinical Examination. Results: Apart from description of results of Objectively Structured Clinical Examination that were generally good, students praised the debriefing session. Ninety percent students thought the timing of debriefing to be perfect. Only 2% percent students complained about negative debriefing. Ten percent students wanted the debriefing session to be conducted in camera so that they could evaluate their own performance. Conclusion: Debriefing session at the end of modular teaching Objectively Structured Clinical Examination is a useful learning tool as not only it provides immediate feedback about the performance but gives students opportunity to discuss own performance with the instructor in order to develop habit of lifelong self-directed adult learner. Keywords: Debriefing, simulation, clinical skill lab